As relações entre ciência e sociedade nas mídias sociais: estudo sobre a comunicação da ciência (pós-pandemia) da Fiocruz no X/Twitter e Instagram - Abreu, Gil Ezequiel Pereira de (2024)
The relationship between science and society can manifest at the interface of social media. The mediating instance of this relationship is Public Communication of Science. This study, within the research line Technologies and Communication Interfaces of the Graduate Program in Technologies, Communication, and Education at the Universidade Federal de Uberlândia, investigated the conditions under which the relationship between science and society occurs on the Fiocruz and Canal Saúde social media platforms X/Twitter and Instagram in a postpandemic context. The research involved conceptualizing definitions of Scientific Culture and Public Science Communication in conjunction with themes of Interaction on social media and with science. The investigation included collecting and observing public data from the pages’ posts to analyze levels and types of interaction in the communication conducted. The exploratory, descriptive, and documental research used Social Media Data Scrap resources, with Lexical Analyses through the Reinert method for thematic category development. Subsequently, Qualitative Content Analyses were conducted in two phases: first on the quantitative data set and then on selected segments of the corpus. The results indicate elements of “scientific journalism” and “scientific dissemination” although this is not the object of the research, therefore, it did not delve conceptually into the terms in the review and analyses. Based on parameters found in the literature, there is no evidence to affirm the presence of Public Communication of Science by Fiocruz and Canal Saúde on the analyzed social media platforms. Regarding public attitudes, there is a polarization and politicization of certain discourses, nonetheless, the public presents interest in participating in science production and influencing decisions. This work is limited as the findings refer exclusively to empirical data found on social media, excluding structural political and institutional issues related to the analyzed institution. It is also limited to investigating aspects of social media comments, without covering other levels related to the dynamics of Instagram and X/Twitter.